1999
DOI: 10.1007/bf01630898
|View full text |Cite
|
Sign up to set email alerts
|

The superior orbital fissure and its contents

Abstract: Topographic landmarks for the superior orbital fissure are useful for general orientation and approach to the middle fossa, cavernous sinus and orbit. In this study, the microsurgical anatomy and morphometry of the superior orbital fissure and its related structures were examined in 57 disarticulated sphenoid bones, 102 skull bases and 58 adult cadaveric heads. The superior orbital fissure was observed in nine different shapes based on the classification of Sharma et al. (1988), and the most frequently observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 9 publications
0
34
0
3
Order By: Relevance
“…Its microsurgical anatomy has been described in detail elsewere. 1,6,7 The nine different shapes, with two major variations defined for the superior orbital fissure in the current literature, become extremely relevant when the surgical target is near or located in the superior orbital fissure. 8,9 These variations in structure may affect not only the clinical expression but also any approach to therapy after injury.…”
Section: Discussionmentioning
confidence: 99%
“…Its microsurgical anatomy has been described in detail elsewere. 1,6,7 The nine different shapes, with two major variations defined for the superior orbital fissure in the current literature, become extremely relevant when the surgical target is near or located in the superior orbital fissure. 8,9 These variations in structure may affect not only the clinical expression but also any approach to therapy after injury.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral wall of the superior orbital fissure can also be divided into upper and lower segments; and the angle between them was found to be 144.27±20.03° (Shi et al 2007). According to Govsa et al (1999), nine different types of shape of the superior orbital fissure were observed based on the classification of Sharma et al (1988) (Fig. 1.13, Table 1.1).…”
Section: Sphenoid Bonementioning
confidence: 99%
“…Natori and Rhoton (1994) measured the distance from the superomedial to the superolateral edges of the superior orbital fissure as 15.9 mm (7.7-22.1 mm), the distance from the superolateral to the inferior edge as 17.6 mm (10-24.3 mm), and the distance from the superomedial to the inferior edge as 7.0 mm (5.6-8.2 mm) (Natori and Rhoton 1995). Govsa et al (1999) found the distance from the superomedial edge to the superolateral edge to be 17.3±3.4 mm on the right side and 16.9±2.9 mm on the left side, the distance from the superolateral to the inferior edge to be 20.8 ±3.9 mm on the right and 20.1±3.8 mm on the left side, and the distance from the superomedial to the inferior edge to be 9.5±2.2 mm on the right and 9.0±2.4 mm on the left side. Another study by Reymond et al (2008) classified the morphology of the superior orbital fissure into nine types.…”
Section: Sphenoid Bonementioning
confidence: 99%
See 1 more Smart Citation
“…The neurosurgical literature also supplies substantial amount of landmarks which are approved by many authors as simple and reliable approaches determining the strategic steps of the operation (13,20,28,31,36,37,38). The importance of the sphenoid bone has been emphasized in many anatomical and neurosurgical studies owing to its central position at the skull base and its significant neurovascular contents (14,23,28,32,33,37). This particular bone has been the subject of much consideration with respect to the new proposals of basic (11,12,17,21,22,41) and alternative surgical techniques (6,9,16,25,42).…”
Section: Introductionmentioning
confidence: 99%